장서개발관리 분야 최근 연구동향 분석에 대한 연구 - 신유미; 박옥남; Shin, You Mi; Park, Ok Nam (Chŏngbo Kwalli Hakhoechi, 2019)
The purpose of this study is to investigate the development direction of future scholarship by analyzing recent research trends in collection development and management field using keyword network analysis. Data was collected from four journals in library and information science field during period of 2003 to 2017. Related articles of Collection Development and Management field were retrieved, and author keywords were extracted from selected papers. Keyword network analysis using NetMiner4 program was performed based on frequency analysis, connection-centered analysis, and parametric analysis. The analysis covers all sections from 2003 to 2017 to look at the changes in research over time, and three sections on five-year basis. As a result, main keywords such as 'open access', 'institutional repository' and 'academic journals' were identified, and topics to be continuously researched were identified. 본 연구는 장서개발관리 분야의 최근 연구동향을 분석함으로써 핵심 연구주제를 파악하고 학문의 지적구조를 규명하고자 하였다. 2003년부터 2017년까지 15년간 문헌정보학 분야 4개 학회지에 등재된 논문 중 장서개발관리 분야의 키워드를 가진 연구논문을 선정하여 저자키워드를 추출하였다. 추출된 저자키워드를 가지고 NetMiner4 프로그램을 이용하여 키워드 네트워크를 구성한 뒤 빈도분석, 연결중심성 분석, 매개중심성 분석을 수행하였다. 분석은 시간의 흐름에 따른 연구 변화를 살펴보기 위하여 2003년부터 2017년까지 전 구간을 대상으로 한 분석과 5년 단위의 3구간으로 나누어 살펴보았다. 연구결과, '오픈액세스', '기관 레포지터리', '학술지' 등의 장서개발관리 분야의 핵심키워드를 파악하고, '대학도서관' 등의 계속 연구될 분야의 주제어를 파악하였다.